DOI: 10.11606/d.3.2007.tde-08082007-172433
|View full text |Cite
|
Sign up to set email alerts
|

Apoio à decisão na seleção do portfólio de projetos: uma abordagem híbrida usando os métodos AHP e programação inteira.

Abstract: Ao professor Antonio Rafael Namur Muscat, pela orientação e pelo constante estímulo transmitido durante todo o trabalho. À professora Marly Monteiro de Carvalho pelas sugestões de referências bibliográficas e pela indicação de especialistas no uso do método AHP, para a elaboração da parte prática deste trabalho. Ao professor Jorge L. Biazzi pela revisão deste trabalho, proposições de melhorias e questionamentos feitos durante a preparação do autor para sua qualificação. Ao professor Roberto Camanho pelo fornec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
6

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 19 publications
0
10
0
6
Order By: Relevance
“…Overall, we carried out two interviews with the same coordinator focusing on the approach of Saaty (2008; and Padovani (2007). We used the paired analysis of criteria and alternatives in the Saaty scale (1-9) ( Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, we carried out two interviews with the same coordinator focusing on the approach of Saaty (2008; and Padovani (2007). We used the paired analysis of criteria and alternatives in the Saaty scale (1-9) ( Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Next, we carried out the normalization of each criterion (average) and for the best visualizations, the values obtained were displayed in percentage (%). For Padovani (2007), this step is important for the application of this method as it allows the analysis of quantitative dimensional elements along with the subjective opinions of the evaluator. A comparative analysis with the weights of CAPES showed that the coordinator's response points to "Faculty" as the most important criterion, followed by "Intellectual Production" and the "Student Body".…”
Section: Inmentioning
confidence: 99%
See 1 more Smart Citation
“…O cálculo da taxa de coerência (T. C.) é dado pela Equação (2). Os valores da taxa de coerência devem estar preferencialmente abaixo de 10% e podem ser aceitáveis até 20%, indicando que não existe viés nos cálculos ou, em outras palavras, que está havendo coerência entre as notas atribuídas a cada critério (PADOVANI, 2007). A etapa 1, consiste na definição das alternativas a serem consideradas, que podem ser compostas por um grupo de lojas de hipermercados presentes em um ou mais estados.…”
Section: Introdução à Técnica Ahpunclassified
“…Many publications discuss matters such as: large number of projects for a limited amount of resources; inadequate decision on whether to carry out or block projects -decisions taken with no availability to reliable information; and large amount of projects of little strategic importance. Some sources mention Nevertheless, the successful implementation of portfolio management is not a trivial task; because it comprises technological and market uncertainties; the negotiation of almost always tight resources between different areas of the company; constant changes due to market instability; the adoption and use of adequate criteria for classification, selection, prioritization and sequencing of projects aiming to align the portfolio with the organization's strategy (VARMA et al, 2008;MAVROTAS;DIAKOULAKI;KOURENTZIS, 2008;MIGUEL, 2008;EISENHARDT;BROWN, 2000;COOPER, 2006;KLEINSCHMIDT, 1999KLEINSCHMIDT, , 2001PADOVANI, 2007;PADOVANI;MUSCAT, 2010). According to McDonaugh III and Spital (2003) the periodic evaluation, blocking the projects that are no longer interesting to the organization and reallocating the resources at greater value-added projects, is a success factor in project portfolio management.…”
Section: Introductionmentioning
confidence: 99%